2014
DOI: 10.1016/j.jcae.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of non-audit services and financial restatements in Malaysia

Abstract: for constructive comments during JCAE Research Seminar held at Monash KL 2012 for a different version of paper. Effiezal would like to thank David Hay, Steven Cahan, John Byong-Tek Lee and seminar participants at University of Auckland. Effiezal would to like to extend his gratitude to Asheq Rahman for some useful insight. We would like to extend our gratitude to Wan Nordin Wan Hussin and the seminar participants at JCAE 2014 for some comments. Research assistance from Marziana Madah Marzuki and Intan Liyana M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 57 publications
(89 reference statements)
4
24
1
Order By: Relevance
“…18 The results of the control variables remain similar to those in Column 1. In the Column 3 full model, LN_NAF is significantly and positively (0.008, p-value=0.01, two-tailed) related to LN_AF, which is consistent with other studies (e.g., Simunic 1984;Abdul Wahab et al 2014). 19 LN_NAF is essential to the testing of hypothesis 2, reported later.…”
Section: Opinionsupporting
confidence: 89%
“…18 The results of the control variables remain similar to those in Column 1. In the Column 3 full model, LN_NAF is significantly and positively (0.008, p-value=0.01, two-tailed) related to LN_AF, which is consistent with other studies (e.g., Simunic 1984;Abdul Wahab et al 2014). 19 LN_NAF is essential to the testing of hypothesis 2, reported later.…”
Section: Opinionsupporting
confidence: 89%
“…The study utilised a well-established model employed in previous studies, for instance, Abdul Wahab et al (2014). The dependent variable is financial restatement (RESTATE), whilst the independent variables are CEO tenure, CEO title, CEO gender, CEO expertise, and CEO age.…”
Section: Model Specificationmentioning
confidence: 99%
“…The second objective is to investigate the impact of types of non-audit services on accruals quality. Several studies (Abdul Wahab et al , 2014; Alexander and Hay, 2013; Huang et al , 2007; Paterson and Valencia, 2011; Walker and Hay, 2013) have suggested that certain types of non-audit services have different effects as related to economic bonding or knowledge spillover on audit services. We segregated the non-audit services as tax-related, audit-related and other non-audit services.…”
Section: Research Aimsmentioning
confidence: 99%
“…Che Ahmad et al (2006) and Abdul Wahab et al (2013, 2014, 2015) examine the relationship between non-audit and audit fees, the propensity of the going-concern audit opinion and financial restatements. The findings are mixed and inconclusive, as some studies identify the support of knowledge spillover (Che Ahmad et al , 2006; Abdul Wahab et al , 2014), whereas others (Abdul Wahab et al , 2013, 2015) identify no such support. However, none of the abovementioned studies examines the impact of non-audit services on accruals quality.…”
Section: Research Aimsmentioning
confidence: 99%